2016
DOI: 10.1007/s10995-016-2144-4
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Care Experiences and Barriers to Care Utilization for Home- and Facility-Delivered Newborns in Uganda and Zambia

Abstract: Objectives The objective of this study was to examine experiences with, and barriers to, accessing postnatal care services, in the context of a maternal health initiative. Methods As part of a larger evaluation of an initiative to promote facility deliveries in 8 rural districts in Uganda and Zambia, 48 focus groups were held with recently-delivered women with previous home and facility deliveries (6 per district). Data on postnatal care experiences were translated, coded and analyzed using thematic content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 29 publications
2
81
0
Order By: Relevance
“…The few studies that have been conducted on postnatal care utilization in Uganda have concentrated on postnatal care beyond 2 days of delivery [20,21], with no attention to factors influencing early postnatal care attendance-the period when maternal deaths are most common. Other studies on Uganda have focused on postnatal care checkups among newborns [20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have been conducted on postnatal care utilization in Uganda have concentrated on postnatal care beyond 2 days of delivery [20,21], with no attention to factors influencing early postnatal care attendance-the period when maternal deaths are most common. Other studies on Uganda have focused on postnatal care checkups among newborns [20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The recent evidence on mistreatment by health care personnel of women in labor and post-natal care has been highlighted as a key barrier for patient centered care. 34,35,36 An important finding to highlight is that despite low formal care seeking levels, 78% of the children were treated with ORT for diarrhea, and 48% with antibiotics for ARI. In contexts with poorly functioning health systems, alternative treatment delivery strategies that provide better access to communities can be strengthened for appropriate treatment for common childhood illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants in a Pakistan study verbalized low quality of maternity care, disrespect and impolite behavior of health professionals (Munawar et al, 2017). On the other hand, Sacks et al, (2017) submitted that a large proportion of their participants reported positive postnatal experiences with more satisfaction among the Zambian than the Ugandan women. The third hypothesis tested in this study found a relationship between maternal satisfaction on the wards and the age and parity of the mother out of all the other selected maternal sociodemographic characteristics tested.…”
Section: Provision Of Postnatal Care Done (%)mentioning
confidence: 99%